Does Early Educational Tracking Increase Migrant-Native Achievement Gaps? Differences-In-Differences Evidence Across Countries - Jens Ruhose; Guido Schwerdt (Center for Economic Studies and ifo Institute (CESifo), 2015)
We study whether early tracking of students based on ability increases migrant-native achievement gaps. To eliminate confounding impacts of unobserved country traits, we employ a differences-in-differences strategy that exploits international variation in the age of tracking as well as student achievement before and after potential tracking. Based on pooled data from 12 large-scale international student assessments, we show that cross-sectional estimates are likely to be downward-biased. Our differences-in-differences estimates suggest that early tracking does not significantly affect overall migrant-native achievement gaps, but we find evidence for a detrimental impact for less integrated migrants.
Keywords: I21; J15; I28; 330; immigration; educational inequalities; educational tracking; differences-in-differences